PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PT. BANK BNI TBK CABANG PAMEKASAN YANG DIMEDIASI OLEH KOMITMEN ORGANISASI - Eko Febriyanto; Chamariyah Chamariyah; Subijanto Subijanto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This type of research is explanatory, namely to test hypotheses between hypothesized variables that will be tested for truth. by using a quantitative approach, the research sample was 96 respondents. In this study, the data will be processed using SEM-PLS data analysis. The aims of this study are: 1) To test and analyze whether motivation has a significant effect on employee performance. 2) To test and analyze whether motivation has a significant effect on organizational commitment. 3) To test and analyze whether organizational commitment has a significant effect on employee performance. 4) To test and analyze whether motivation has an indirect effect on employee performance mediated by organizational commitment. The results showed that: 1) Motivation has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.286 and the p-values of 0.007. 2) Motivation has a positive and significant effect on organizational commitment. This is evidenced by the original sample value of 0.501 and the p-values of 0.000. 3) Organizational commitment has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.429 and the p-values of 0.000. 4) Motivation has a significant positive effect on employee performance mediated by organizational commitment. This is evidenced by the original sample value of 0.215 and the p-values of 0.002.